Innovative methods to test and monitor the preload in mechanical fasteners. Issue 1 (20th April 2021) - Reiterer, Michael
Abstract: The paper presents currently applied methods to test and monitor the preload level in mechanical fasteners and evaluates them with respect to the quality of the gained measuring results. Both, visual inspection methods and electronic state‐of‐the‐art measurement techniques are presented. This contribution introduces recently developed and patented innovative methods to test and monitor the preload level in mechanical fasteners. The methods developed include a smart mechanical fastener with pressure indicator and a smart electronic measuring screw nut. The smart mechanical fastener has no electronic features and is able to display the loss of preload through a red dot that occurs on the upper end of the fastener. The smart measuring screw nut is an electronic fastening element, that records the current value of preload in a time‐discrete or permanent manner. In order to investigate the suitability for daily use and long‐term stability of the novel methods to test and monitor the preload in mechanical fasteners, laboratory experiments and in‐situ tests were executed. The gained results are presented and discussed.